L'efficienza rispetto alla frontiera delle possibilità produttive Modelli teorici ed analisi empiriche - Laureti, Tiziana (Studi e saggi, 2006)
The evaluation of the performance of a private or public company, based on the concepts of productivity and efficiency, must be carried out using suitable methodological tools, specifically identified within a production theory. The volume offers an overview of the evolution of the concept of efficiency - and in particular of technical efficiency with respect to production possibilities - and of the methodologies related to measurement problems, through an exposition that examines both the theoretical aspects and the practical ones, with particular reference to the academic environment.